2010
DOI: 10.1063/1.3428731
|View full text |Cite
|
Sign up to set email alerts
|

Cantilevered bimorph-based scanner for high speed atomic force microscopy with large scanning range

Abstract: A cantilevered bimorph-based resonance-mode scanner for high speed atomic force microscope ͑AFM͒ imaging is presented. The free end of the bimorph is used for mounting a sample stage and the other one of that is fixed on the top of a conventional single tube scanner. High speed scanning is realized with the bimorph-based scanner vibrating at resonant frequency driven by a sine wave voltage applied to one piezolayer of the bimorph, while slow scanning is performed by the tube scanner. The other piezolayer provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…The EC-HS-AFM setup used in this work was developed based on our previous homemade HS-AFM system. , To achieve high-speed imaging during electrochemical cycling, two major requirements should be satisfied. One of them was the use of a small cantilever (BioLever mini, BL-AC40TS-C2, Olympus, Japan) with a ∼25 kHz resonance frequency in an aqueous solution because this bandwidth was adequate for high-speed imaging at the rate of ∼1 frame/s in the contact mode.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The EC-HS-AFM setup used in this work was developed based on our previous homemade HS-AFM system. , To achieve high-speed imaging during electrochemical cycling, two major requirements should be satisfied. One of them was the use of a small cantilever (BioLever mini, BL-AC40TS-C2, Olympus, Japan) with a ∼25 kHz resonance frequency in an aqueous solution because this bandwidth was adequate for high-speed imaging at the rate of ∼1 frame/s in the contact mode.…”
Section: Methodsmentioning
confidence: 99%
“…In the present work, we developed an EC-HS-AFM technique by combining our previous homemade HS-AFM system , with cyclic voltammometry, which enabled nanoscale imaging at the rate of ∼1 frame/s during the electrochemical cycling. Spinel LiMn 2 O 4 was chosen as a cathode electrode because it is one of the promising cathode materials for the LIBs due to its high operation voltage, high energy density, low toxicity, and low cost.…”
Section: Introductionmentioning
confidence: 99%
“…In our experimental setup, fast scan ( x -axis) was realized by using a resonance-type piezoelectric bimorph scanner [ 41 , 42 ]. Traditional piezo tube scanner provides slow scan ( y -axis) and motion in z -axis for keeping an average height to the sample surface while imaging in high speed [ 20 , 24 , 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…s an important method to study the dynamic process in the nanometer scale, high-speed atomic force microscopy (AFM) has been paid considerable attention in the last decade. Great progress has been made in technical areas such as designing new cantilevers with smaller dimensions, [1][2][3] high-speed scanners, 1,2,[4][5][6][7] feedback circuit in z-direction with high bandwidth, [8][9][10] as well as measurement modes of operation. [11][12][13] It is well known that operation modes, mainly including constant-force 11) and tapping 14) ones, are important functions and have been widely used in conventional AFM for imaging.…”
mentioning
confidence: 99%
“…Recently, it has been shown that AFM images can be taken at high speed in the constant-height mode, where the sample is controlled to maintain an average height by the feedback system. 5) The feedback system consists of various devices including a cantilever, a detector for sensing cantilever deflection, a feedback circuit, and a z-scanner that moves the sample stage in the z-direction. While imaging at high speed in constant-height mode, the cantilever tip is held in contact with the sample surface and the flexural deflection of the cantilever is used to measure the local height of the surface.…”
mentioning
confidence: 99%